Genetic Box: Character, Validity, Practicality, and Effectiveness as A Learning Media - Susiani; Jamilah; Khalifah Mustami; Syahriani; Azmi Fathin Eka Nugraha (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
This study employed research and development (R & D) with a four-dimensional development model that includes four stages: define, design, develop, and disseminate. This research aimed to determine the characteristics, level of validity, practicality, and effectiveness of genetic box learning media for class XII genetic material at SMA Negeri 22 Bone. The genetics box learning media is a product that is being developed and will be tested through validity, practicality, and effectiveness tests. The research subjects were 29 class XII students at SMA Negeri 22 Bone. The instruments in this study included student and educator response questionnaires to obtain product practicality data, media characteristic sheets to obtain the characteristics of the developed genetics box media, and learning achievement tests to obtain product effectiveness data. According to the findings of this study, the media have an appealing appearance, are clear and neat, and use appealing color combinations. Genetic box media is easy to operate and does not require electronic facilities or equipment to use. In addition, the genetics box has value in helping students understand the material and can provide a comprehensive learning experience. The genetics box media also has quite good tool durability because it is made of hard materials such as wood and boards. The genetics box media formulates learning objectives and refers to material items that support the achievement of those objectives. In addition, the genetics box learning media for class XII genetic material at SMA Negeri 22 Bone has a validity level of expert validity and a material expert value of 3.72 with a very valid category. The response of students and educators to the level of practicality is worth a total of 3.52 in the positive category. The learning achievement test of students using the genetics box learning media on genetic material for class XII at SMAN 22 Bone is in the effective category because it reaches 100%, so the genetics box learning media for class XII genetic material at SMAN 22 Bone is feasible to use because it meets valid, practical, and effective criteria.